2007
DOI: 10.1007/s10856-007-3219-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro corrosion behaviour of Mg alloys in a phosphate buffered solution for bone implant application

Abstract: The corrosion behaviour of Mg-Mn and Mg-Mn-Zn magnesium alloy in a phosphate buffered simulated body fluid (SBF) has been investigated by electrochemical testing and weight loss experiment for bone implant application. Long passivation stage and noble breakdown potential in the polarization curves indicated that a passive layer could be rapidly formed on the surface of magnesium alloy in the phosphate buffered SBF, which in turn can protect magnesium from fast corrosion. Surfaces of the immersed magnesium allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(88 citation statements)
references
References 12 publications
6
78
1
3
Order By: Relevance
“…Zinc is a common alloying element in magnesium, and helps overcome the harmful corrosive effect of impurities such as iron and nickel, thus improving the corrosion resistance of magnesium alloys [27]. Xu et al [28] also proposed that the addition of zinc into magnesium could improve the corrosion resistance. Zirconium is usually used as a grain refiner in magnesium alloys without aluminum, thereby contributing to the strength of these alloys and reducing the adverse effects of iron contaminants on the corrosion resistance of magnesium alloys [29,30].…”
Section: Mgclmentioning
confidence: 99%
“…Zinc is a common alloying element in magnesium, and helps overcome the harmful corrosive effect of impurities such as iron and nickel, thus improving the corrosion resistance of magnesium alloys [27]. Xu et al [28] also proposed that the addition of zinc into magnesium could improve the corrosion resistance. Zirconium is usually used as a grain refiner in magnesium alloys without aluminum, thereby contributing to the strength of these alloys and reducing the adverse effects of iron contaminants on the corrosion resistance of magnesium alloys [29,30].…”
Section: Mgclmentioning
confidence: 99%
“…Zinc is a common alloying element added in magnesium and its strengthening effect is second only to aluminum (21). Xu et al (13) proposed that the addition of zinc in magnesium could improve the corrosion resistance. Zirconium is usually used as a grain refiner in magnesium alloys, thereby contributing to the strength of these alloys (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that magnesium alloys have good biocompatibility, may promote osteocyte growth and may induce production of osteoblasts and osteocytes (11)(12)(13)(14)(15). Owing to suitable mechanical property and good biocompatibility, high specific strength and specific stiffness, degradable magnesium alloys can be utilized in many aspects such as bone repair material, coronary artery stent and porous repair material.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Mn, as a component of Mg alloys, consists of the improvement of corrosion resistance and may increase the plasticity of Mg alloys [383,399]. Zn improves the strength of Mg alloys [399,400] and their corrosive resistance [401]. However, its influence on increased cytotoxicity was identified [402,403].…”
Section: Selection Of Materials Of Implantable Devices In Regenerativmentioning
confidence: 99%